Immunosenescence in the wild? A longitudinal study in a long‐lived seabird. Issue 2 (10th December 2021) - Bichet, Coraline; Moiron, Maria; Matson, Kevin D.; Vedder, Oscar; Bouwhuis, Sandra
Abstract: Longitudinal studies of various vertebrate populations have demonstrated senescent declines in reproductive performance and survival probability to be almost ubiquitous. Longitudinal studies of potential underlying proximate mechanisms, however, are still scarce. Due to its critical function in the maintenance of health and viability, the immune system is among the potential (mediators of) proximate mechanisms that could underlie senescence. Here, we studied three innate immune parameters—haemagglutination titre, haemolysis titre and haptoglobin concentration—in a population of common terns ( Sterna hirundo ) known to undergo actuarial senescence. We repeatedly sampled birds of known sex and age across 11 years and used random regression models to (a) quantify how immune parameters vary among individuals and (b) describe within‐individual age‐specific changes in, and potential trade‐offs between, immune parameters. Our models revealed no differences between males and females in haemagglutination titre and haptoglobin concentration, and very low among‐individual variation in these parameters in general. Within individuals, haemagglutination titre increased with age, while haptoglobin concentration did not change. We found no indication for selective (dis)appearance in relation to haemagglutination titre or haptoglobin concentration, nor for the existence of a trade‐off between them. Haemolysis was absent in the majority (76%) of samples. Common terns do not exhibit clear senescence in haemagglutination titre and haptoglobin concentration and show very little among‐individual variation in these parameters in general. This may be explained by canalisation of the immune parameters or by the colonial breeding behaviour of our study species, but more longitudinal studies are needed to facilitate investigation of links between species' characteristics and immunosenescence in wild animals. Abstract : Longitudinal studies investigating proximate mechanisms of senescence are scarce, and the immune system could be one of these. Using an individual‐based long‐term study, the authors study three immune parameters of 396 known‐aged and repeatedly sampled common terns. They did not detect any evidence for immunosenescence and little among‐individual variation in general.